Prey C:P ratio and phosphorus recycling by a planktivorous fish: advantages of fish selection towards pelagic cladocerans - Reissig, Mariana (2015)
Prey selection by the small planktivore Galaxias maculatus and phosphorus gain depending on diet has been examined related to predator–prey daily distribution. Prey elemental composition (C:P ratio) was analysed as a factor of selectivity. Field experiments were carried out to evaluate the effect of prey on phosphorus recycling. Results revealed that the pelagic cladoceran Ceriodaphnia dubia was a highly selected prey by all fish sizes at dawn and dusk, despite its low abundances in comparison with other zooplankters, while the littoral were ingested only during day. The high selectivity for C. dubia showed that G. maculatus moved to pelagic zone during night to consume this prey but returned to littoral areas during day due to the increase in predation risk. Analysis of elemental composition revealed that P content of C. dubia was significantly higher than other planktonic or littoral prey (Bosmina longirostris, Boeckella gracilipes and chironomids). Phosphorus recycling experiments showed that G. maculatus would transport and supply P in available forms for primary producers. Fish size was observed to influence P recycling as YOY had significant higher mass-specific P release in the morning and mid-day when they preyed mainly upon C. dubia. Low prey C:P ratio appears as a factor that would add benefits to the classical visual fish selection towards cladocerans, as this preference would imply a net phosphorus gain for fish.